Uneven recovery and a lingering food crisis during the COVID-19 pandemic for rural safety net transfer recipients in Ethiopia - Gilligan, Daniel O.; Berhane, Guush; Hirvonen, Kalle; Kumar, Neha; Leight, Jessica (International Food Policy Research Institute, 2022)
In the first few months of the COVID-19 pandemic, researchers at IFPRI and elsewhere worked quickly with their partners in government, the private sector, and survey firms to provide evidence on the immediate impacts of the COVID-19 health crisis and related restrictions in low- and middle-income countries (LMICs). However, systematic evidence on the effects of the crisis has been more limited in the ensuing months up to and after the one-year anniversary of the pandemic. Early analysis of economic models of the crisis suggested that its economic effects would be severe in the short run and greatest in Africa south of the Sahara, where the pandemic and related lockdowns were projected to depress incomes of both urban workers and rural households (Laborde, Martin, and Vos 2021). Phone surveys and rapid assessments conducted in the first weeks of the pandemic reported significant job losses in both rural and urban areas (Wieser et al. 2020), disruptions to urban food value chains (Tamru, Hirvonen, and Minten 2020), and declines in household dietary diversity in Addis Ababa (Hirvonen, de Brauw, and Abate 2021). In the time since those initial projections and rapid surveillance surveys were conducted, researchers have revisited the same samples to analyze the medium-term effects of the pandemic. In addition, they have gathered information on households at the economic margins of society and those considered to be less affected by the pandemic by virtue of their sector of employment or remote location.